Countertransference in the treatment of PTSD - Wilson, John P.; Lindy, Jacob D. (Guilford, 1994)
I. Theoretical and conceptual foundations of countertransference in post-traumatic therapies * Empathic strain and countertransference / John P. Wilson and Jacob D. Lindy * Empathic strain and therapist defense: Type I and II CTRs / John P. Wilson, Jacob D. Lindy and Beverley Raphael * Empathic strain and countertransference roles: Case illustrations / Jacob D. Lindy and John P. Wilson II. Countertransference in the treatment of victims of sexual, physical, and emotional abuse * The dance of empathy: A hermeneutic formulation of countertransference, empathy, and understanding in the treatment of individuals who have experienced early childhood trauma / I. Lisa McCann and Joseph Colletti * Countertransference in the treatment of multiple personality disorder / Richard P. Kluft * Inner city children of trauma: Urban violence traumatic stress response syndrome (U-VTS) and therapists' responses / Erwin Randolph Parson * Countertransference in the treatment of acutely traumatized children / Kathleen Nader * Rape and the phenomena of countertransference / Carol R. Hartman and Helene Jackson III. Countertransference reactions in work with victims of war trauma, civil violence, and political oppression * Countertransference in the treatment of Southeast Asian refugees / J. David Kinzie * Determinant factors for countertransference reactions under state terrorism / Inger Agger and Soren Buus Jensen * Countertransference in the treatment of war veterans / Michael J. Maxwell and Cynthia Sturm * Countertransference and World War II Resistance fighters: Issues in diagnosis and assessment / Wybrand Op den Velde, G. Frank Koerselman and Petra G. H. Aarts IV. Countertransference in "at-risk" professionals: Rescue workers, mental health providers, and persons at the workplace * When disaster strikes: Managing emotional reactions in rescue workers / Beverley Raphael and John P. Wilson * Trauma and countertransference in the workplace / Christine Dunning * Countertransference, trauma, and training / Yael Danieli